2021
DOI: 10.3389/fcomm.2021.671429
|View full text |Cite
|
Sign up to set email alerts
|

Speech Rate Adjustments in Conversations With an Amazon Alexa Socialbot

Abstract: This paper investigates users’ speech rate adjustments during conversations with an Amazon Alexa socialbot in response to situational (in-lab vs. at-home) and communicative (ASR comprehension errors) factors. We collected user interaction studies and measured speech rate at each turn in the conversation and in baseline productions (collected prior to the interaction). Overall, we find that users slow their speech rate when talking to the bot, relative to their pre-interaction productions, consistent with hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…In the present study, speakers showed a systematic Alexa-DS speech style: when talking to Alexa, speakers produced sentences with a slower rate, higher mean f0, and higher f0 variation, relative to human-DS. These differences align with prior work showing slowed speech rate toward Alexa socialbot (Cohn et al, 2021), increased higher mean f0 in speech toward voice-AI (Raveh et al, 2019), and greater segmental lengthening in computer-DS (Burnham et al, 2010). Furthermore, both an increased mean f0 and f0 variation are consistent with increased vocal effort in response to a presumed communicative barrier; for instance, prior work has reported that speakers produce greater f0 variation in response to a word FIGURE 4 | Mean acoustic changes from speakers' citation form productions to the interaction with the Interlocutors (Alexa vs. human) for vowel duration (milliseconds, ms), F1 (log Hertz, Hz), and F2 (log Hertz, Hz).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, speakers showed a systematic Alexa-DS speech style: when talking to Alexa, speakers produced sentences with a slower rate, higher mean f0, and higher f0 variation, relative to human-DS. These differences align with prior work showing slowed speech rate toward Alexa socialbot (Cohn et al, 2021), increased higher mean f0 in speech toward voice-AI (Raveh et al, 2019), and greater segmental lengthening in computer-DS (Burnham et al, 2010). Furthermore, both an increased mean f0 and f0 variation are consistent with increased vocal effort in response to a presumed communicative barrier; for instance, prior work has reported that speakers produce greater f0 variation in response to a word FIGURE 4 | Mean acoustic changes from speakers' citation form productions to the interaction with the Interlocutors (Alexa vs. human) for vowel duration (milliseconds, ms), F1 (log Hertz, Hz), and F2 (log Hertz, Hz).…”
Section: Discussionsupporting
confidence: 88%
“…We do not observe register-level differences in speech rate in the present study, as has been observed in related work (e.g., Cohn et al, 2022; but see Cohn, Liang, et al, 2021;. Here, speakers produce similar speech rate adjustments for voice-AI and human addressees.…”
Section: Production and Perception Of Device-directed Speechsupporting
confidence: 87%
“…A higher pitch has only been reported for two other studies for device-DS, one in German (voice assistant) 19 and one in French (robot) 23 . Duration increases (or decreased speech rate) is a more commonly reported feature of technology-DS for adults (e.g., for a computer avatar 10 or imagined computer 44 , or Alexa socialbot 16 , or social robot 21 ). In the current study, adults and children made both duration and pitch adjustments, supporting routinized interaction theories of human–computer interaction 43 , in which people have distinct modes of engaging with technology than with other humans.…”
Section: Discussionmentioning
confidence: 99%